An age- and sex-specific dietary guidelines index is a valid measure of diet quality in an Australian cohort during youth and adulthood - Johanna E. Wilson; Leigh Blizzard; Seana L. Gall; Costan G. Magnussen; b; Wendy H. Oddy; Terence Dwyer; Alison J. Venn; Kylie J. Smith (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Measuring diet quality over time is important due to health impacts, but to our knowledge, a Dietary Guidelines Index (DGI) with consistent scoring across childhood/adolescence (youth) and adulthood has not been validated. We hypothesized that a DGI that reflected age- and sex-specific guidelines would be a valid measure of diet quality in youth and adulthood. The DGI is based on the 2013 Australian Dietary Guidelines to reflect current understanding of diet quality and comprises 9 indicators, with a maximum score of 100 points. DGI scores were calculated for participants of the Australian Childhood Determinants of Adult Health study, which included a 24-hour food record during youth (1985, n = 5043, age: 10-15 years) and a 127-item food frequency questionnaire during adulthood (2004-2006, n = 2689, age: 26-36 years). We evaluated construct validity (distribution of scores, principal components analysis, correlation with nutrient density of intakes) and criterion validity (linear regression with population characteristics). DGI scores were multidimensional in underlying structure and normally distributed. Among youth, a lower DGI was significantly associated (P < .05) with smoking and with lower academic achievement and socioeconomic status. DGI scores were negatively correlated with energy, sugar, and fat and positively correlated with fiber, protein, and micronutrients. Among adults, a lower DGI was associated with lower education and self-reported health and higher waist circumference, insulin resistance, and total and low-density lipoprotein serum cholesterol. The DGI is an appropriate measure of diet quality in youth and adulthood because higher scores reflect nutrient-dense, rather than energy-dense, intake and discriminate between population characteristics consistent with the literature. (C) 2019 Elsevier Inc. All rights reserved.